ENCLAVING ATAS TANAH HAK GUNA USAHA SEBAGAI SUMBER TANAH UNTUK PEMBANGUNAN PERUMAHAN BAGI MBR DIKAITKAN DENGAN PENATAAN RUANG - Mas Guntur Wiraprana; Martin Roestamy (Magister Hukum Sekolah Pascasarjana Unida, 2019)
The purpose of this research is: 1) To know and analyze about enclaving on the cultivation rights title as a land source for low-income people housing development, 2) To know and analyze the role of the regional government in spatial planning organizing on cultivation rights title of the enclave of the land as a land source for low-income people housing development.This research use normative legal research method with qualitative approach. The results of this research is: 1) enclaving on the prolongation or renewal of the cultivation rights title can be used as a land source for the housing development for low-incomwe people, with a terms that its still concerned with the suitability and design on the spatial planning in that area, 2) regional governments as the representatives of the state in the regions authorized in planning, utilizing and controlling spatial in their regions, especially on the regional spatial planning policies, granting licenses, and giving punishment to anyone who violating the regional regulations. enclaving on the cultivation rights title as a land source for low-income people housing development must suitable with the spatial allocation that allows housing / flats to be built.